Risk factors associated with HSV-2 sero-prevalence and, the level of symptom recognition among women in inner city Johannesburg - implications for public health interventions - Mlaba, Nonkululeko Zamaximba (My University, 2009)
Background: Herpes Simplex Virus type 2 (HSV-2) is a common cause of genital ulcers worldwide and has emerged as a co-factor in human immunodeficiency virus (HIV) acquisition and transmission. A study was conducted to determine the prevalence of HSV-2, its correlates, the accuracy of reported history of genital ulcer disease (GUD) to predict HSV-2 infection and the extent of symptom recognition in a clinic population in Johannesburg. Methods: 210 women aged 18 years or older were interviewed and socio-demographic, sexual behaviour and clinical information collected. Serological testing for HSV-2 and HIV infections was performed, but only where sera were available for the latter. Factors associations with HSV-2 infection were assessed using logistic regression to estimate odds ratios (OR) and 95% confidence intervals (CI). The sensitivity, specificity, predictive values and likelihood ratios of a history of GUD were calculated. Results: The estimated sero prevalence of HSV-2 was 73% (95% CI 67% - 79%). Few participants, 13/206 (6%) participants had knowledge of genital herpes. Only 9/203 (4%) participants recognised lesions of genital herpes following education and counselling about HSV-2 infection. HSV-2 infection was associated with older age(>25 years of age) OR 2.6 (95% CI 1.4-5.0), spending more than 2 nights away from home, OR 6.0 (95% CI 1.0-62.7), having more than 2 sexual lifetime partners, OR 2.2 (95% CI 1.1-3.9), a history of an STI in the past 3 months ,OR 3.6 (95% CI 1.2-9.5) and HIV infection, OR3.3( 95%CI 1.4-7.9). A history of genital ulceration performed poorly as a predictor of HSV-2 seropositivity; the sensitivity was 7% and specificity was 96%. Conclusion: HSV-2 prevalence was high and few participants were aware of their infection. HVS-2 infection was associated with risky sexual behaviour .A history of genital ulcer disease was not sufficient as a diagnostic tool for HSV-2 infection. Public health interventions should focus on behavioural modification and increasing awareness of genital herpes. HSV-2 management should be incorporated into HIV care and STI protocols.
M.P.H., Faculty of Health Sciences, University of the Witwatersrand, 2009
Keywords: herpes simplex; HSV-2 infection; Johannesburg; symptoms; public health